Da‘wah in the Disruption Era: Reorienting Entrepreneurial Innovation through Islamic Ethics and Philosophy - Azizah, Rahmi Nur; Cecep Castrawijaya (Yayasan Abdurrauf Cendekia Nusantara, 2025)
The disruption era compels Islamic da‘wah institutions to adopt entrepreneurial innovations to remain relevant and sustainable. This transformation creates a dilemma between preserving spiritual missions and exploiting emerging economic opportunities, thereby requiring a comprehensive ethical examination. This study aims to analyze the philosophical foundations and Islamic ethical principles underlying entrepreneurial practices in da‘wah institutions, and to evaluate how the maq??id al-shar?‘ah framework can function as a safeguard against mission drift amid increasing commercialization of religious activities. Employing a qualitative library research method, this study examines literature on da‘wah entrepreneurship, Islamic ethics, maq??id al-shar?‘ah, and the dilemmas associated with the commercialization of da‘wah. The findings indicate that entrepreneurial innovation can leverage opportunities provided by digitalization and socio-economic collaboration to expand social impact, yet also carries the risk of shifting institutional focus when profit-oriented motives take precedence over spiritual objectives. Islamic ethics and the principles of maq??id al-shar?‘ah serve as essential guidelines for balancing business orientation with da‘wah missions through transparent governance, internal audits, and collective education. This study concludes that the success of entrepreneurial innovation within da‘wah institutions in the disruption era is determined not only by operational efficiency and economic reach but also by the ability to maintain moral integrity and deliver sustainable social benefits. [Era disrupsi menuntut lembaga dakwah untuk mengadopsi inovasi kewirausahaan agar tetap relevan dan berkelanjutan. Fenomena ini menimbulkan dilema antara mempertahankan misi spiritual dan mengeksploitasi peluang ekonomi, sehingga memerlukan kajian etika yang komprehensif. Penelitian ini bertujuan menelaah landasan filosofis dan etika Islam dalam praktik kewirausahaan lembaga dakwah, serta menilai bagaimana maq??id al-syar?‘ah dapat berfungsi sebagai rambu untuk mencegah terjadinya mission drift di tengah arus komersialisasi dakwah. Penelitian ini menggunakan metode library research dengan pendekatan kualitatif, menganalisis literatur terkait inovasi kewirausahaan lembaga dakwah, etika Islam, maq??id al-syar?‘ah, dan dilema komersialisasi dakwah. Hasil kajian menunjukkan bahwa inovasi dapat memanfaatkan peluang digitalisasi dan kolaborasi sosial-ekonomi untuk memperluas dampak sosial, namun berpotensi menimbulkan risiko pergeseran misi ketika orientasi profit menguat. Etika Islam dan maq??id al-syar?‘ah menjadi pedoman penting untuk menyeimbangkan orientasi bisnis dengan tujuan dakwah melalui governance yang transparan, audit internal, dan pendidikan kolektif. Kajian ini menegaskan bahwa keberhasilan inovasi kewirausahaan lembaga dakwah di era disrupsi tidak hanya ditentukan oleh efisiensi operasional, tetapi juga oleh kemampuan menjaga integritas moral dan kebermanfaatan sosial secara berkelanjutan.]